Talent Management: Strategies For Recruiting And Retaining High Performing Employees - Budi Rismayadi (Journal of Economics and Business (JECOMBI), 2024)
In a competitive business era, companies are required to develop sophisticated talent management strategies to attract, manage and retain high-potential individuals. This research aims to investigate talent management practices that are effective in recruiting and retaining high performing employees in the work environment. This research uses a qualitative approach with descriptive methods. The research results show that implementing talent management strategies that focus on employee development, creating a positive work environment, and increasing open communication contribute significantly to talent retention in an organization. Employees who feel valued, have opportunities for career growth, and are involved in the company's shared goals tend to be more satisfied and engaged. These factors, such as a pleasant work experience, effective communication, and alignment of company values with mission, have a positive impact on employee satisfaction levels and play a role in maintaining workforce stability and productivity. Thus, the research results support this strategy as an effective approach in grooming and retaining high-performing talent in an organization.